Do women manage land more sustainably than men? Evidence from 10-year Uganda soil fertility management panel data - Nkoyna, Ephraim (International Food Policy Research Institute, 2017)
Presented by Ephraim Nkoyna (IFPRI), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.)